Umidade do solo e disponibilidade hídrica na zona das raízes em condições naturais de caatinga preservada - Costa, Carlos Alexandre Gomes (2012)
Regarding ecohydrology, the catchment water is distributed over several important compartments. Many studies in semiarid re gions indicate the surface reservoirs as the main water compartments. However, the watershed has greater scope than the water reservoirs contained therein, and water resources in compartments distributed in the watershed (like in soil) should be analyzed not only with regard to ecological uses, but also as spaces of water availability. Therefore, the object ive of this work was to analyze, based on measurements and modeling, the water dynamics in th e soils of a semi-arid basin in preserved Caatinga, and its impact on water availability. Wit h this in mind, it was measured, among others, the soil moisture, every hour, from 2003 to 2010 (2923 days) in the Aiuaba Experimental Basin (AEB, 12 km ²), fully preserved and with average annual rainfall of 560 mm. Monitoring was carried out through three TDR se nsors, one installed in each of the three soil and vegetation associations (SVA) identified in the basin. The research method considered six main steps: i) assessment of the eff ective root depth of preserved Caatinga ii) calibration of humidity TDR sensors iii) space-time representation of soil moisture in each SVA unit iv) analysis of soil water availability in the root zone, v) parameterization of the WASA-SED hydrological model, and vi) parameterizati on of the DiCaSM hydrological model. The results of this research indicate the importance of addressing the temporal analysis of soil moisture and soil water availability in the root zone to maintain the Caatinga biome. More specifically, it was observed that the effecti ve depth of the root system on AEB ranged between 70 and 80 cm in areas with deep soils, but in areas with shallow soils, it was observed that the effective depth of the roots had adapted to the constraints, having been reduced to less than 40 cm. Furthermore, the season al analysis showed that in the dry season, the roots have lengths up to 11 cm smaller, openin g, therefore, secondary pores that facilitate the penetration of what little rain water falls in the dry months (June-December), as well as in the first rains of the wet season. In the two SVAs whose soils are deep and the vegetation is dense, the soil water is 'not available' (ie below the permanent wilting point - WP) during nearly nine months a year (72% of the time), and on ly during three months of the year (25% of the time) the soil water is available. In the re maining 3% of the year (about 10 days) there is gravitational water in these SVAs. In the SVAs whose soil is shallow and whose vegetation is sparse, the dynamics of soil water are different : the time when there is gravitational water, available and unavailable, is practically the same (four months a year). This is due to, among other things, the low soil moisture at the permanen t wilting point of the Udorthent, and to its limited thickness, generating saturation much more frequently than in others that - unlike this one - have deep drainage. The depletion of soil wat er under conditions of moisture below the wilting point was another important result of this research. In the two associations with deep soils and thick vegetation, it was observed – throu ghout the observation period – continuous fall of moisture level until it approached asymptot ically the residual moisture. More detailed analysis showed that the reduction of soil moisture between the WP and the residual moisture level always followed the exponential decay. It was observed, in the association of shallow soil and sparse vegetation, that the moisture did not fall to below the WP, even subjected to the same rigorous climate of the other associations . Considering: (i) that in such a dry soil, the drainage is unlikely, and (ii) that the associated processes of percolation and evaporation should not be responsible for the removal of soil w ater either (since the phenomenon is not observed in SVAs whose soil is shallow and therefor e warmer) , it is raised the hypothesis that the soil drying under these conditions must be caused by water extraction by vegetation. This would strengthen the argument that the Caating a has adapted to survive under water stress. The hydrological models WASA-SED and DiCaSM failed to adequately represent the temporal dynamics of soil water in the AEB. However , the models did satisfactorily reproduce the retention curves of soil moisture, al lowing the representation of the water availability in the root zone for planning purposes . Finally, we managed to evaluate - quantitatively, spatially and temporally – the soil water availability. This availability is of the same order of magnitude of the availability of an o ptimal surface reservoir. The availability in the soil, in quantitative terms, can be almost five times higher than that of the surface reservoir. However, the security associated with su rface water (90%) is much higher than the water permanence available in the AEB: just 28% in areas with deep soils and 65% in areas with shallow soils.